1991
DOI: 10.1126/science.254.5035.1183
|View full text |Cite
|
Sign up to set email alerts
|

Radical Reactions of C 60

Abstract: Photochemically generated benzyl radicals react with C(60) producing radical and nonradical adducts Rn C(60) (R = C(6)H(5)CH(2)) with n = 1 to at least 15. The radical adducts with n = 3 and 5 are stable above 50 degrees C and have been identified by electron spin resonance (ESR) spectroscopy as the allylic R(3)C(60)(.) (3) and cyclopentadienyl R(5)C(60)(.) (5) radicals. The unpaired electrons are highly localized on the C(60) surface. The extraordinary stability of these radicals can be attributed to the ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
475
1
16

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 896 publications
(512 citation statements)
references
References 8 publications
12
475
1
16
Order By: Relevance
“…C60 fullerene, as a radical sponge, inactivates multiple circulating free radicals, thus having the potential to stop free radical injury and to halt the progression of diseases caused by excess free radical production (33)(34)(35). It is well known that C60 can effectively protect against all of the principal damaging forms of ROS: hydrogen peroxide, hydroxyl radical, and superoxide (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…C60 fullerene, as a radical sponge, inactivates multiple circulating free radicals, thus having the potential to stop free radical injury and to halt the progression of diseases caused by excess free radical production (33)(34)(35). It is well known that C60 can effectively protect against all of the principal damaging forms of ROS: hydrogen peroxide, hydroxyl radical, and superoxide (35).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that C60 can effectively protect against all of the principal damaging forms of ROS: hydrogen peroxide, hydroxyl radical, and superoxide (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C 60 -fullerenes, owing to their electronic structure as electron-poor polyolefines, are highly reactive towards various organic radicals 3 and have drawn considerable attention in the area of antioxidant research. An electron paramagnetic resonance analysis has shown that C 60 derivatives, such as carboxyfullerene, fullerenol and hexa(sulfobutyl)fullerene, have excellent capabilities to scavenge deleterious reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%